Ablation of endothelial prolyl hydroxylase domain protein‐2 promotes renal vascular remodelling and fibrosis in mice. Issue 9 (7th March 2017) - Wang, Shuo; Zeng, Heng; Chen, Sean T.; Zhou, Liying; Xie, Xue‐Jiao; He, Xiaochen; Tao, Yong‐Kang; Tuo, Qin‐hui; Deng, Changqin; Liao, Duan‐fang; Chen, Jian‐Xiong
Abstract: Accumulating evidence demonstrates that hypoxia‐inducible factor (HIF‐α) hydroxylase system has a critical role in vascular remodelling. Using an endothelial‐specific prolyl hydroxylase domain protein‐2 (PHD2) knockout (PHD2 EC KO) mouse model, this study investigates the regulatory role of endothelial HIF‐α hydroxylase system in the development of renal fibrosis. Knockout of PHD2 in EC up‐regulated the expression of HIF‐1α and HIF‐2α, resulting in a significant decline of renal function as evidenced by elevated levels of serum creatinine. Deletion of PHD2 increased the expression of Notch3 and transforming growth factor (TGF‐β1) in EC, thus further causing glomerular arteriolar remodelling with an increased pericyte and pericyte coverage. This was accompanied by a significant elevation of renal resistive index (RI). Moreover, knockout of PHD2 in EC up‐regulated the expression of fibroblast‐specific protein‐1 (FSP‐1) and increased interstitial fibrosis in the kidney. These alterations were strongly associated with up‐regulation of Notch3 and TGF‐β1. We concluded that the expression of PHD2 in endothelial cells plays a critical role in renal fibrosis and vascular remodelling in adult mice. Furthermore, these changes were strongly associated with up‐regulation of Notch3/TGF‐β1 signalling and excessive pericyte coverage.